STRATEGI RETORIKA PEMBAWA ACARA DALAM MATA NAJWA DI TRANS7 - Imaz Nafiza (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This study aims to interpret the function of verbal and nonverbal rhetorical forms of presenters in Mata Najwa on Trans7 as a rhetorical strategy. The design and type of this research used descriptive qualitative. The research was conducted comprehensively which refers to the analysis of verbal and nonverbal rhetorical forms. Data collection techniques used recording techniques, listening techniques, and note-taking techniques. Meanwhile, the data analysis in this study was to classify the data and classify the data. To test the validity of the data, the researchers used several stages, namely credibility testing, transferability testing, depenability testing, and confirmability testing. The results of this study found that the use of verbal (diction and style) and nonverbal (body language) rhetoric from Najwa Shihab's speech contained many persuasive elements. From the persuasive element, it was used as a strategy for the presenter in Mata Najwa on Trans7.Based on the results and discussion of verbal and nonverbal rhetoric in the Mata Najwa program on Trans7, various verb elements were selected which functioned to expedite the process of the presenter's strategy in influencing listeners. Therefore, an art in communicating is absolutely necessary for a presenter in conveying messages through the rhetoric of verbal forms of speech and rhetoric of speech in nonverbal forms.